2022
DOI: 10.1093/icesjms/fsab262
|View full text |Cite
|
Sign up to set email alerts
|

Destructive outbreaks of the corallivorous starfish Acanthaster cf. solarisspare coral assemblages in the shallowest reef flat areas in New Caledonia

Abstract: Outbreaks of the corallivorous starfish Acanthaster cf. solaris (COTS) are not fully understood, especially in the shallowest areas behind the reef crests where limited COTS impacts are often reported. Here, we investigated the outbreak occurrence and compared post-outbreak habitat impacts in reef flats vs. upper fore reefs at 13 sites in New Caledonia. In this Pacific territory so far considered marginally affected by COTS, we documented wide occurrences of aggregations, combining massive population increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Field observations during various pilot campaigns in New Caledonia and Vanuatu have confirmed that double injections of vinegar are highly effective in culling COTS, particularly when extreme densities (e.g. > 5000 COTS.ha -1 , Buttin 2018, Dumas et al 2022) place considerable human, financial and logistical constraints on more conventional manual collection methods. However, there are still uncertainties about the physiological processes involved in the death of the COTS starfish exposed to vinegar.…”
Section: Discussionmentioning
confidence: 98%
“…Field observations during various pilot campaigns in New Caledonia and Vanuatu have confirmed that double injections of vinegar are highly effective in culling COTS, particularly when extreme densities (e.g. > 5000 COTS.ha -1 , Buttin 2018, Dumas et al 2022) place considerable human, financial and logistical constraints on more conventional manual collection methods. However, there are still uncertainties about the physiological processes involved in the death of the COTS starfish exposed to vinegar.…”
Section: Discussionmentioning
confidence: 98%